Chemistry, manufacturing, and controls for live microbial products: addressing classification challenges and enhancing process validation - Slijkerman, Ralph; van Dijk, Rob; Mohieddin, Nasser; Ciarlante, Ivana; de Jong, Antal; Schuler, Moira Monika (Frontiers in Microbiomes, 2025)
Traditional process validation life cycles need to be tailored to the specific needs of live microbial products (LMPs). LMPs can be divided into subcategories, and the product characteristics are the basis for the regulatory category and thereby the applicable guidelines. All LMPs fall under regulations related to GMP-compliant manufacturing; however, there are live microbial specific challenges. Both the FDA and the EMA do not have a regulatory framework for LMPs administered by injection. Full adherence to general guidelines for injectables is technically not feasible for LMPs, as sterility is required, which stands in conflict with living organisms as a product. Safety-related critical quality attributes (CQAs) of such LMPs typically include the absence of contaminants and proof of monoseptic condition of the product. This paper aims to holistically outline and compare LMP-relevant guidelines while highlighting different subcategories. Additionally, the status of the field is captured by collecting all LMP-related clinical trials to resolve specific challenges in LMP development. Taken together, this overview will aid in bringing future LMPs from development to commercialization.